Assessment of Drugs Approved by Public Knowledge‐Based Applications (Kouchi‐shinsei) During the Last Two Decades in Japan. Issue 4 (2nd July 2021) - Maeda, Hideki; Fukuda, Yuka; Uchida, Marika
Abstract : Public knowledge‐based application (" Kouchi‐shinsei " in Japanese) is unique to Japan, implemented to eliminate the off‐label use of unapproved indications, dosages, and administrations because of drug lag. The guidance for public knowledge‐based application was issued in 1999. This study comprehensively investigated the trends of items approved by public knowledge‐based application in Japan during the last 2 decades. Prescription drugs approved from January 2000 to December 2019 were surveyed. In Japan, 1, 855 drugs were approved within the target survey period. Among them, 219 (11.8%) were approved by public knowledge‐based application. Considering the changes in the number of items approved by public knowledge‐based application over the years, the number of items approved in 2000 was 7, reaching a maximum of 34 items in 2011, and decreased after that, 8 items were approved in 2019. The regulatory characteristics of drugs approved by public knowledge‐based application and those of other drugs were compared. By public knowledge‐based application, more anticancer and pediatric drugs were approved ( P  < 0.001), and only one drug for orphan diseases was approved ( P  < 0.001). In addition, the review time of public knowledge‐based applications was significantly shorter than that of normal applications regardless of time point. The approval system using public knowledge‐based application began in 2000, following issuance of the "Guidance for off‐label use of prescription drugs." Furthermore, the approved items were mostly drugs for cancer, infectious diseases, and pediatric drugs. We anticipate the promotion of public knowledge‐based application to accommodate the approval of drugs for orphan diseases.